Pengaruh Perilaku Konsumsi Mahasiswa Ekonomi Islam Unesa Terhadap Keputusan Pembelian Online di Marketplace Tokopedia - Zainardi, Muhammad Daffa Irza; Fahrullah, (Universitas Negeri Surabaya, 2022)
The growing era was followed by the development of the buying and selling system that existed in the community. Currently, many marketplaces can meet customer needs by offering an online buying and selling system, one of which is Tokopedia. The consumption behavior of each individual can have an impact on purchasing decisions. This study aims to identify the consumption behavior of Islamic Economics Students, at the State University of Surabaya on online purchasing decisions in the Tokopedia marketplace using simple linear regression. This method is used to test variables with quantitative analysis. Questionnaires were distributed via google forms to respondents who were selected using a purposive sampling technique by determining the number of samples using the Slovin formula. Respondents' answers that have been collected are measured using a Likert scale. The findings of this study, it is stated that the consumption behavior of Islamic Economics Students at the State University of Surabaya influences online purchasing decisions in the Tokopedia marketplace.